Tame those guinea fowl - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Moussa Gueme Bournebe, of the Direction des Pêches et de l Aquaculture, BP 447, N djamena, Chad tells of his eleven years experience as a raiser of hooded guinea fowl. 'They are easy to domesticate. You just need to collect their eggs from...